2021
DOI: 10.7705/biomedica.5712
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencia de anticuerpos y seroconversión frente a Rickettsia spp. en pacientes atendidos en instituciones de salud del departamento de Caldas, Colombia, 2016-2019

Abstract: Introducción: Las rickettsiosis son enfermedades zoonóticas, algunos artrópodos cumplen el papel de vectores. la inespecificidad de los síntomas hace que su diagnóstico clínico sea difícil. La Inmunofluorescencia indirecta (IFI), se usa en el diagnóstico. En Colombia, a partir del 2003, ha resurgido el interés por realizar estudios en búsqueda de dicha patología. Objetivo: Caracterizar epidemiológicamente los casos humanos compatibles con rickettsiosis que consultan a las instituciones de salud del depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…This finding is consistent with other national studies where the seroprevalence using a titer cutoff value of ≥1:128 has been estimated between 25.6% and 26.7% 15 , 16 , 23 ; other studies, with titer cutoff values of ≥1:64 or lower, have reported 32–60% seropositivity, which makes comparison with the current study unreliable. 33 35 Miraflores is a mountainous territory, part of the Eastern Cordillera of the Andean Mountain range. Its economy is based largely on agriculture and livestock 32 ; therefore, it was not surprising to find properties with crop fields and a larger number of domestic animals associated with household seropositivity.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other national studies where the seroprevalence using a titer cutoff value of ≥1:128 has been estimated between 25.6% and 26.7% 15 , 16 , 23 ; other studies, with titer cutoff values of ≥1:64 or lower, have reported 32–60% seropositivity, which makes comparison with the current study unreliable. 33 35 Miraflores is a mountainous territory, part of the Eastern Cordillera of the Andean Mountain range. Its economy is based largely on agriculture and livestock 32 ; therefore, it was not surprising to find properties with crop fields and a larger number of domestic animals associated with household seropositivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the last two decades, as documented in the scientific literature, confirmed and suspected autochthonous human cases have been described in Brazil, 69,73 Mexico, [74][75][76][77][78][79][80] Colombia, [81][82][83][84][85] Nicaragua, 86 and Honduras (Figure 1B). 87 In addition, murine typhus was reported in a young Dutch girl after visiting Suriname (her length of visit and time of symptom onset supported infection while traveling).…”
Section: Contemporary Perspective Of Murine Typhus In Latin Americamentioning
confidence: 98%
“…In Colombia, individuals sampled at two different time periods (2010-2011 and 2016-2019) by indirect IFA demonstrated 25% (172/682) and 2% (3/175) IgG seropositivity, respectively, against R. typhi at a titer of 64 or greater and without cross-reactivity to Rickettsia rickettsii and R. felis antigens. 83,85 In Mexico, a study published in 2000 described a seroprevalence of 17% to R. typhi in 1,400 healthy blood donors from Mexico City. 98 Subsequent studies of rural populations from Yucatan state during 2015-2018 demonstrated IgG or IgM antibodies to R. typhi in 2% (6/354) and 13% (13/99), respectively.…”
Section: Contemporary Perspective Of Murine Typhus In Latin Americamentioning
confidence: 99%
“…Several years later, a prospective study performed in the same region, specifically in Aguadas, Filadelfia, and Salamina municipalities, evidenced several SFG and TG rickettsioses [ 196 ]. Finally, in another surveillance study, eight febrile patients enrolled in the municipalities of Belalcázar, Salamina, Filadelfia, Noracasia, and San José were confirmed as SFG and TG rickettsioses [ 197 ]. These studies confirm that murine typhus and at least one pathogenic SFG Rickettsia sp.…”
Section: Rickettsiamentioning
confidence: 99%